The Implementation of the Cooperative Integrated Reading and Composition (CIRC) Model on Students' Cooperation Attitudes at SDN 160 Palembang - Iga Mawarni; Midya Botty; Ayu Nur Shawmi (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This research is motivated by the problem of the lack of cooperation attitudes among second-grade students at SDN 160 Palembang, where interaction and collaboration within groups are still limited. To address this challenge, the study aims to describe the process of implementing the Cooperative Integrated Reading and Composition (CIRC) learning model and to analyze the supporting and inhibiting factors. Using a descriptive qualitative approach, this study involved the teacher and second-grade students of class II D as subjects. Data were collected through observation, interviews, and documentation, and were then analyzed using the Miles and Huberman interactive model, with validation through triangulation. The results of the study show that the CIRC model successfully fostered students' cooperation attitudes, self-confidence, and communication. This success was supported by the teacher's creativity and the use of effective learning media. However, the implementation of the model was hindered by an unfavorable classroom environment and limited time allocation. The study concludes that the CIRC model is effective, but it requires better classroom management strategies to achieve optimal results.